2019
DOI: 10.1038/s41598-019-44677-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Safe Isolation of Human Peripheral Blood B and T Lymphocytes through Spiral Microfluidic Channels

Abstract: Peripheral blood lymphocytes (PBLs) are mature lymphocytes that circulate in the blood rather than being localized to organs. A reliable label-free collection approach that can viably and appropriately isolate PBLs to establish in vitro culture systems is crucial for basic research and clinical requirements. However, isolation of PBLs from whole blood is difficult, and so the development of a rapid and safe method to perform this task is required. Microfluidic technology offers opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…As one of the major antigen-presenting cells (APCs), and as part of the innate immune system, macrophages, especially the M1 phenotypes, are capable of secreting various proinflammatory cytokines and controlling the activation of the adaptive immune system, such as T cells and their effector phenotypes. The activation of T cells usually occurs in the spleen and is presented in the peripheral blood as mature circulating lymphocytes [ 38 ]. In NAFLD, it has been shown that Treg cells appear to have an overall tempering effect, while CD4 + and CD8 + T cells were more likely to induce liver damage and fibrosis progression, aggravating the burden of NAFLD and inflammation [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…As one of the major antigen-presenting cells (APCs), and as part of the innate immune system, macrophages, especially the M1 phenotypes, are capable of secreting various proinflammatory cytokines and controlling the activation of the adaptive immune system, such as T cells and their effector phenotypes. The activation of T cells usually occurs in the spleen and is presented in the peripheral blood as mature circulating lymphocytes [ 38 ]. In NAFLD, it has been shown that Treg cells appear to have an overall tempering effect, while CD4 + and CD8 + T cells were more likely to induce liver damage and fibrosis progression, aggravating the burden of NAFLD and inflammation [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to solve the above problem, a biomimetic microwell-based microfluidic chip platform is presented here for the long-term culture of the single coral polyps, which can conveniently be combined with the microscopy. Compared with the traditional culture method, the microfluidic culture platform is advantageous in feasibly and precisely controlling the local cellular microenvironment and monitoring the growth state of the cultured living organisms in real time and in situ [20][21][22] . The platform can provide an adjustable microenvironment to control the temperature, light intensity and fluid composition, which can easily be assembled and disassembled based on different experimental requirements.…”
mentioning
confidence: 99%
“…This pool of selection builds on the classical passive micromixer approaches such as the previously developed herringbone micromixer, but most of them (Figure 1b,c,e–g,i) are appealing to creeping flow based microfluidic applications. Spiral microchannels (Figure 1a) are mainly used for particle separation [27] or isolation [28] but they have also been assessed with respect to their mixing efficiency capabilities [29]. This type of mixing enhancement increases the mixing channel length while still restraining the chip surface area.…”
Section: Micromixing Methodsmentioning
confidence: 99%